Effect of Ce doping on the resistance of Na over V2O5-WO3/TiO2 SCR catalysts. (August 2018) - Hu, Guang; Yang, Jian; Tian, Yuanmeng; Kong, Bowen; Liu, Qingcai; Ren, Shan; Li, Jiangling; Kong, Ming
Graphical abstract: Highlights: Different forms of Na poisoning CeO2 -V2 O5 -WO3 /TiO2 catalysts were prepared by impregnation method. The comparison of the poisoning effect between Na2 O and NaCl over Ce10 VWTi catalyst was studied. The poisoning effect of Na2 O is lighter than that of NaCl because the 4Na2 O-Ce10 VWTi catalyst exists more acid sites. The reasons contributing to the catalytic activity and Na poisoning resistance of CeVWTi catalyst were proposed. Abstract: Enhanced performance of Ce doping on the catalytic activity of V2 O5 -WO3 /TiO2 catalysts and its resistance properties to Na poisoning have been investigated in the research. Different Na species (NaCl and Na2 O) were deposited on CeO2 -V2 O5 -WO3 /TiO2 catalysts by impregnation method. The results presented that CeO2 -V2 O5 -WO3 /TiO2 catalysts exhibited a higher NH3 -SCR activity and better Na resistance than the V2 O5 -WO3 /TiO2 catalyst, and its poisoning resistance to Na2 O is more superior than to NaCl, caused by more acid sites over the 10%CeO2 -V2 O5 -WO3 /TiO2 (Ce10 VWTi) catalyst, which indicated that the poisoning resistance of Na2 O on Ce10 VWTi catalysts is higher than that of NaCl. Combined with the characterization results, the dopant of Ce could enhance the surface chemisorbed oxygen on the Na poisoning V2 O5 -WO3 /TiO2 catalysts, facilitate the redox cycle, and increase the intensity of acid sites due to the newly formed Brønsted acid sites stemmed from C e 3 + − N H 4 +, thereby promoting catalytic activity and Na poisoning resistance.